Instrumen Penilaian diri Sebagai Salah Satu Penilaian Dimensi Gotong Royong Peserta Didik pada Pelaksanaan Projek Penguatan Profil Pelajar Pancasila - Nurzanah Sri Hastuti; Samsun Samsun; Indah Mustika Rini; Awaluddin Tjalla; Lussy Dwi Utami (Syntax Idea)
P5 is an initiative aimed at strengthening students' profiles in implementing the values of Pancasila, with a focus on the theme of Sustainable Lifestyle. In order to assess the extent to which this self-assessment instrument can be used as a reliable measurement tool, this research sets out to evaluate the validity and reliability of the instrument. The purpose of this study is to determine whether the self-assessment instrument created as one of the measures of the students' mutual cooperation dimension in the collaboration element with sub-elements of cooperation and positive interdependence in the Strengthening Pancasila Student Profile Project (P5) at SMA Negeri 2 Cileungsi meets the minimum requirements to be considered a good measurement tool in terms of instrument validity and reliability. This research is categorized as Research and Development. The validity testing of this self-assessment instrument uses Aiken's V test, and its item reliability is reviewed using Cronbach's Alpha. Data collection for this study involves teachers who have undergone training on the implementation of P5, resulting in the development of a self-assessment instrument that is then tested on tenth-grade students, totaling 376 participants involved in the implementation of P5 with the theme of Sustainable Lifestyle. By analyzing student responses to the self-assessment questionnaire that measures the dimension of mutual cooperation in the collaboration element with sub-elements of Cooperation and positive interdependence in the implementation of P5, the validity and reliability levels are determined. The validity test results indicate that the validity coefficients in the mutual cooperation dimension are significantly valid at the 1% level for each instrument item. The reliability test results obtained an Alpha coefficient value of 0.805 for the cooperation sub-element and 0.709 for the positive interdependence sub-element, indicating that the assessment instrument can be considered reliable. Thus, it can be concluded that the tested self-assessment instrument is valid and reliable, making it suitable for measuring the dimension of mutual cooperation among students in the implementation of P5.